2018
DOI: 10.1371/journal.pone.0190245
|View full text |Cite
|
Sign up to set email alerts
|

Regulating BMI1 expression via miRNAs promote Mesenchymal to Epithelial Transition (MET) and sensitizes breast cancer cell to chemotherapeutic drug

Abstract: Polycomb group (PcG) proteinB lymphoma Mo-MLV insertion region 1 homolog (BMI1) is a transcriptional repressor that plays an important role in human carcinogenesis. MicroRNAs (miRNAs) are endogenous small non-coding RNAsthat implicate a negative regulation on gene expression. Deregulation of the expression of miRNAs has been implicated in tumorigenesis. Here, we have shown that knock-down ofBMI1increases theexpression of tumor-suppressivemiRNAs. Elevated levels of expression of miR-200a, miR-200b, miR-15a, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Undoubtedly, research related to tumorigenicity in terms of miRNA regulation is critically needed. miRNAs are RNA molecules of approximately 22 nucleotides in length that bind to the 3′-untranslated region (3′-UTR) of their respective target genes and exert their influence on gene expression by either inhibiting protein translation or degrading mRNA [35]. miRNAs are known to be an integral component of cancer development [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, research related to tumorigenicity in terms of miRNA regulation is critically needed. miRNAs are RNA molecules of approximately 22 nucleotides in length that bind to the 3′-untranslated region (3′-UTR) of their respective target genes and exert their influence on gene expression by either inhibiting protein translation or degrading mRNA [35]. miRNAs are known to be an integral component of cancer development [35].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are RNA molecules of approximately 22 nucleotides in length that bind to the 3′-untranslated region (3′-UTR) of their respective target genes and exert their influence on gene expression by either inhibiting protein translation or degrading mRNA [35]. miRNAs are known to be an integral component of cancer development [35]. We noted that the DEmiRNA hsa-miR-182 (connection degree = 13) had the highest connection degree among the prognostic DEmiRNAs (hsa-miR-182 and hsa-miR-183) in the ceRNA network, suggesting an obvious influence of hsa-miR-424 on HCC pathogenesis and prognosis (Additional file 5: Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are known to be an integral component of cancer development [17][18][19]. Several studies have highlighted the role of miR-182-5p in the development of different cancers [13,14].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…Epithelial integrity requires the stability of E-cadherin/β-catenin complexes (25). Previous studies have reported that Snail, β-catenin and EMT contribute to tumor chemotherapeutic resistance to sorafenib (26) and cisplatin (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%